A squid-based beam current monitor for FAIR/CRYRING. (26th November 2015) - Geithner, Rene; Kurian, Febin; Reeg, Hansjörg; Schwickert, Marcus; Neubert, Ralf; Seidel, Paul; Stöhlker, Thomas
Abstract: A SQUID-based beam current monitor was developed for the upcoming FAIR-Project, providing a non-destructive online monitoring of the beam currents in the nA-range. The cryogenic current comparator (CCC) was optimized for lowest possible noise-limited current resolution together with a high system bandwidth. This CCC is foreseen to be installed in the CRYRING facility ( CRYRING@ESR: A study group report www.gsi.de/fileadmin/SPARC/documents/Cryring/ReportCryring_40ESR.PDF ), working as a test bench for FAIR. In this contribution we present results of the completed CCC for FAIR/CRYRING and also arrangements that have been done for the installation of the CCC at CRYRING, regarding the cryostat design.